Quenching of para-H-2 with an ultracold antihydrogen atom (H)over-bar(1s) - Sultanov, Renat A.; Adhikari, Sadhan Kumar [UNESP]; Guster, Dennis (Amer Physical Soc, 2010)
In this work we report the results of calculation for quantum-mechanical rotational transitions in molecular hydrogen, H-2, induced by an ultracold ground-state antihydrogen atom (H) over bar (1s). The calculations are accomplished using a nonreactive close-coupling quantum-mechanical approach. The H-2 molecule is treated as a rigid rotor. The total elastic-scattering cross section sigma(el)(epsilon) at energy epsilon, state-resolved rotational transition cross sections sigma(jj)'(epsilon) between states j and j', and corresponding thermal rate coefficients k(jj)' (T) are computed in the temperature range 0.004 K less than or similar to T less than or similar to 4 K. Satisfactory agreement with other calculations (variational) has been obtained for sigma(el)(epsilon).